Big Data and Consumer Participation in Privacy Contracts: Deciding who Decides on Privacy - Rhoen, Michiel (Utrecht Journal of International and European Law, 2015)
Big data puts data protection to the test. Consumers granting permission to process their personal data are increasingly opening up their personal lives, thanks to the “datafication” of everyday life, indefinite data retention and the increasing sophistication of algorithms for analysis.The privacy implications of big data call for serious consideration of consumers’ opportunities to participate in decision-making processes about their contracts. If these opportunities are insufficient, the resulting rules may represent special interests rather than consumers’ needs. This may undermine the legitimacy of big data applications.This article argues that providing sufficient consumer participation in privacy matters requires choosing the best available decision making mechanism. Is a consumer to negotiate his own privacy terms in the market, will lawmakers step in on his behalf, or is he to seek protection through courts? Furthermore is this a matter of national law or European law? These choices will affect the opportunities for achieving different policy goals associated with the possible benefits of the “big data revolution”.